AMIR’S GUILT IN KHALED HOSSEINI’S THE KITE RUNNER - Lordna G.L. Lambe; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2013)
This paper emphasizes guilt as the main issue portrayed in Khaled Hosseini’s The Kite Runner through its main character, Amir. Guilt discussed in this paper is defined as a feeling produced from a behavior that is related to a failure, a wrong doing, or even a sin. This paper discusses the way Amir deals with his guilt since it needs to be redeemed even through suffering. In this paper, I maintain that Amir bears not only his personal guilt yet also his familial and societal guilt. Amir’s personal guilt comes from his failure to become a good friend, his familial guilt comes from his burden to bear the sin of the family, especially his father, and his societal guilt comes from his burden to bear the injustice that happened in the history of his tribe. The analysis also shows that self-sacrifice is the way Amir chooses to deal with his guilt.